The effect of mathematics anxiety on the achievement of middle school students in Amman - Bahjat Hamid Altakhyneh (Intelektual Pustaka Media Utama, 2020)
This study aims to investigate whether student anxiety about the subject of mathematics has any effect on the achievement of middle-school students in Amman, Jordan. It also aims to investigate whether student gender plays a role. The study sample consists of 180 seventh grade students enrolled in Amman public schools during the 2018/2019 academic year. These are distributed into three levels of anxiety as displayed by the students: low, middle, and high. Then, math anxiety measurements are collected, the validity and reliability for which are verified. The results reveal that there are statistically-significant differences in achievement between the middle level of math anxiety and the two other extremes. It is found that middle anxiety level have a positive effect on achievement, whereas for low and high math anxiety levels, no differences in achievement are perceived. In addition, no statistically significant differences (α more equal than 0.01) were found between males and females with regards to math anxiety; and there is no interaction between the level of math anxiety and gender in achievement.